2007
DOI: 10.1016/j.jesp.2006.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Basic human values: Inter-value structure in memory

Abstract: Three experiments examined the latent structure of values. Participants rated the importance of values clustered in pairs. Based on [Schwartz, S. H. (1992). Universals in the content and structure of values: Theoretical advances and empirical tests in 20 countries. In M. Zanna (Ed.), Advances in Experimental Social Psychology (Vol. 25, pp. 1-65). San Diego, CA: Academic Press.] circular model, we predicted and found that the time to rate the second value in each pair was shorter when the two values were motiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
63
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 34 publications
6
63
0
1
Order By: Relevance
“…It is activated when cognitive requirements are complex, and SMA activity is mainly driven by increased attentional and working memory load, not by response inhibition per se (Criaud & Boulinguez, 2013). This corroborates the results of our study, where cognitive demands including attention and self-reflection are likely to have been high and a 4-s response window allowed the completion of meaningful decisional processing (see Pakizeh et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…It is activated when cognitive requirements are complex, and SMA activity is mainly driven by increased attentional and working memory load, not by response inhibition per se (Criaud & Boulinguez, 2013). This corroborates the results of our study, where cognitive demands including attention and self-reflection are likely to have been high and a 4-s response window allowed the completion of meaningful decisional processing (see Pakizeh et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…Replicating past evidence (Pakizeh et al, 2007), paired-samples t-test showed that participants took (Fig. 3).…”
Section: Response Timesupporting
confidence: 71%
See 3 more Smart Citations